Evaluation of the influence of starch addition on polyurethane properties - Cruz, Carolina Konzen (2022)
Polyurethanes are among the most versatile polymers in the world with great demand in today's market. The development of new compositions is necessary, due to the search for high performance materials and with properties different from the existing ones. Incorporating fillers into the polymer is a means of improving the performance of polyurethane. Thus, the present work aimed to incorporate starch into thermoplastic polyurethane via in situ polymerization, in proportions of 1.0%, 2.0%, 3.0% and 5.0% by mass in relation to the mass of pure polymer, and evaluate the thermal and morphological properties of the composites obtained. Polyurethane was obtained through the reaction of polycaprolactonediol (PCL) and hexamethylene 1,6-diisocyanate (HDI). The morphology of the composites obtained was characterized by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Thermal properties were characterized by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). In addition, the surface of the polymers was evaluated using the wettability technique. Based on the results obtained, the composite that presented the best performance was polyurethane with 5% starch, as it showed an increase in crystallinity and, therefore, an increase in thermal resistance. In addition, the best dispersion of the filler in the polymer matrix was verified for the microcomposite with 5% starch, indicating that the starch added distinct properties to the composite.